Graphing Jane Austen - Carroll, J. author. aut Link
XI, 305 p.
Keywords: This book helps to bridge the gap between science and literary scholarship. Building on findings in the evolutionary human sciences, the authors construct a model of human nature in order to illuminate the evolved psychology that shapes the organization of characters in nineteenth-century British novels, from Jane Austen to E. M. Forster.